Determinants of Learning Outcomes and Satisfaction with Online Teaching Based on Students’ Perception - Suitability of Applying the Instrument (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Research on perceived learning outcomes and student satisfaction with online university education, as well as defining determinants of critical success factors in online teaching, is on the rise. Determining the key success factors, i.e. determinants of online teaching success, is extremely important, especially now that all higher education institutions have been forced to try their hand at teaching through technology (TBL – technology-based learning). The research presented in this paper was conducted on a sample of 360 students of the University of Novi Sad at different levels and types of studies, using the PLS structural equation modelling. A questionnaire that is a synthesis of Virtual Learning Environment models and Learning Frameworks through techniques was applied. The motivation for the research was to prove that the same instrument can be applied in Serbia, i.e. on data collected from students at the University of Novi Sad. The following were selected as dependent variables: learning outcomes and student satisfaction with teaching. Independent variables were presented with constructs: intrinsic and extrinsic motivation, dialogue and cooperation between students, but also student-lecturer, course design, and student self-regulation during learning, and were observed as potential determinants of online learning outcomes in terms of user satisfaction and learning outcomes. After data processing, the applied instrument proved to be extremely suitable and useful. The research presented in this paper is among the first ones done on the topic of success of the online lectures during the pandemic in Serbia.